Ultrasound guided fine needle aspiration cytology in deep seated lesions: an effective diagnostic tool - Bajantri, Supriya R.; Mehta, Dhara P.; Shah, Purva C.; Patel, Ragini A. (International Journal of Research in Medical Sciences, 2022)
Background: Fine needle aspiration cytology (FNAC) is a diagnostic method used to assess various masses in the body with minimal invasion. FNAC alone has a lower yield as compared to biopsy for diagnosing deep-seated lesions. Radiological guidance improves the yield of FNAC. The aim of the study was to evaluate the diagnostic efficacy of Ultrasound (USG) guided FNAC in various deep-seated lesions in the body. We conducted a cross-sectional analytical study at the cytology section of pathology department of our hospital for indoor patients. Methods: It was a retrospective study done over a period of five years, which included 334 aspirates suspected to be of inflammatory or neoplastic origin obtained from deep-seated lesions. After a thorough clinical and radiological evaluation, USG guided FNACs were performed. Experienced pathologists processed the smears, prepared thereby, for cytological evaluation and diagnosis. Results: A total of 334 samples were collected using USG-guided FNAC. The most common site was lungs (36.5%) followed by liver (13.77%). The most common type were malignant lesions (57.19%) which were either primary malignancies or metastatic carcinomas. 29 samples were found to be acellular or had inadequate material, thus a diagnosis couldn’t be made. Out of the various lung masses, non-small cell carcinoma was the most common (66.39%). The most common liver mass was metastatic carcinoma (54.35%). Conclusions: USG guided FNAC is a relatively simple, safe, fast, minimally invasive and cost effective procedure, which provides quite a high rate of adequacy and diagnostic efficacy. It is useful for making a pre-operative diagnosis and guiding the choice of treatment.